INGLIZ VA O‘ZBEK TILLARIDA GRAMMATIK KATEGORIYALARNING QIYOSIY TAHLILI - Rasulova Dildora Abduqahhor qizi; Allayev Zafar (International Journal of Literature and Language Studies, 2026)
This article analyzes the comparative typology of grammatical categories in English and Uzbek languages. The study examines the categories of case, parts of speech, tense, mood, voice and person-number, as well as their grammatical functions and means of expression. The analytical nature of English and the agglutinative structure of Uzbek are discussed through these grammatical categories. The results show that although both languages possess similar grammatical categories, their structural realization differs significantly. The findings of the study may contribute to comparative linguistics, translation studies and foreign language teaching methodology.